Relationship Between Learning Motivation, Learning Dicipline and Teaching Materials Against Student Competence TKR Department of Automotive Productive Training Through Readiness of Student Learning as an Intervening Variable - Sulistiono, Dwi; Syamwil, Rodia; Florentinus, Totok Sumaryanto (Journal of Vocational and Career Education, 2018)
This Research aims to determine the learning effect of motivation, discipline, materials on student learning readiness; to find out learning of motivation, discipline, materials towards the competencies of automotive productive training eye students. The method used is description analysis with linear regression. This analysis is used to determine whether there is an learning effect of motivation, discipline and materials on the competencies of students in automotive productive training eyes with intervening learning readiness. The research subjects were class XI students of SMK Bhakti Praja Batang. Data collection is questionnaire. Descriptive data analysis, validity, normality and regression analysis. The results showed directly that there was a significant effect of learning motivation on student competency, direct significant influence of learning discipline on student competency, direct significant effect of teaching material on student competence, and directly there was a significant effect of motivation on learning readiness, directly there is no significant effect of motivation on learning readiness, direct significant effect of learning readiness on student competence. Indirect effect is mediated by the intervening variable of learning readiness. Independent variables do not affect students' competencies through intervening variables, so that intervening variables are not used as reinforcement between independent and dependent variables.